A morphometric approach and recircumscription of the Stachytarpheta longispicata complex (Verbenaceae) - Cardoso, Pedro Henrique; Menini Neto, Luiz; Somavilla, Nádia Silvia; Trovó, Marcelo (European Journal of Taxonomy, 2022)
The Stachytarpheta longispicata complex is a group of seven accepted infraspecific taxa endemic to the Brazilian Cerrado, defined by its pedicellate flowers with salmon or dark red corollas. Due to the great morphological variation and very brief original descriptions, these taxa have controversial circumscriptions. We evaluated the morphological variation through the morphometric analysis of 11 natural populations in addition to nomenclatural types to assess the current infraspecific circumscriptions and clarify the limits of these taxa. A set of 36 continuous vegetative and reproductive characters was measured for each of the 115 specimens sampled, encompassing the morphological variability in the group and its geographic distribution. A compiled data matrix formed the basis for the multivariate analysis (UPGMA, PCA, and DA). Our results recovered five consistent groups corresponding to the four subspecies, and all three recognised varieties treated in the same morphological group. Quantitative and qualitative characters not previously studied in detail are important to delimit the five groups. A taxonomic rearrangement is proposed for the complex, circumscribing five distinct species: Stachytarpheta brevibracteata, S. longipedicellata, S. longispicata, S. minasensis, and S. ratteri. The taxonomic treatment includes four new combinations and names at new rank, two new synonyms, and one lectotype. Descriptions, an identification key, geographical distribution map, illustrations, and provisional conservation assessments are also provided.